2022
DOI: 10.1186/s12871-022-01705-6
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia personnel’s visual attention regarding patient monitoring in simulated non-critical and critical situations, an eye-tracking study

Abstract: Background Cognitive ergonomics design of patient monitoring may reduce human factor errors in high-stress environments. Eye-tracking is a suitable tool to gain insight into the distribution of visual attention of healthcare professionals with patient monitors, which may facilitate their further development. Methods This prospective, exploratory, high-fidelity simulation study compared anesthesia personnel’s visual attention (fixation count and dwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Besides the approaches to audiovisual data analysis described in the previous sections of this report, audiovisual monitoring interfaces play an integral role in various domains, including air traffic control [EBL*23], control rooms [SFLD22, HHG*12], anesthesia [AQH*21,RMS*22], neurology [LCS*28], dermoscopy [WRK*19], surgery [Zie23], network monitoring [Wor19a,AHvR*21], automotive [JDS15,XWX*22], to name a few.…”
Section: Adjacent Topicsmentioning
confidence: 99%
“…Besides the approaches to audiovisual data analysis described in the previous sections of this report, audiovisual monitoring interfaces play an integral role in various domains, including air traffic control [EBL*23], control rooms [SFLD22, HHG*12], anesthesia [AQH*21,RMS*22], neurology [LCS*28], dermoscopy [WRK*19], surgery [Zie23], network monitoring [Wor19a,AHvR*21], automotive [JDS15,XWX*22], to name a few.…”
Section: Adjacent Topicsmentioning
confidence: 99%
“…In an eye-tracking study of anesthesia personnel, visual attention to 15 areas of interest on the patient monitor was measured [ 21 ]. Results showed that a few vital signs commanded the most attention, namely blood pressure (BP), expiratory carbon dioxide, and electrocardiogram (ECG).…”
Section: Reviewmentioning
confidence: 99%